Computational drug repositioning using big data from genetic studies - Zhang, Wen (Journal of Applied Science, Engineering, Technology, and Education, 2019)
This mini-review gives the development of computational drug repositioning using big data from perspective of genetic study. The reverse profile principle is utilized to reposition drug hits by investigating gene expression, genotyping and GWAS data. Several big data sets are introduced, which are remarkable references that utilized for the genetic studies. Relevant computational genetics methods and the developments are briefly described as well. This review aims to give insights into this area so as to raise more ideas as well as to attract more attentions for this ascendant field. With the development of information technology and engineering applications, prosperous results are highly expected.